The effect of color on the attention level - Fouziah Md Yassin; M. S. Latip; Ag. Asri Ag. Ibrahim; S. Baco; A. Alias (Faculty of Science and Natural Resources, 2021)
Color plays important role in learning and educational, communication, marketing and architecture. From the previous research especially related to educational, color could affect the attention level of people. The present study was undertaken to find out if the turquoise color could trigger the attention level to be equal or above the attention threshold. The required threshold to start or operate the electronic device should be equal or more than 40. The attention level of five (5) respondents were recorded when they were looking at turquoise color for 10 seconds using a single electrode of Neurosky Mindwave headset. From the experiment, it is found that turquoise could trigger the attention level of all respondents to be above the attention threshold of 40 if they are thoroughly trained.